Análise crítica propositiva para fixação, limitação e revisão da multa periódica - Salles, Nélio Zattar de Mello Carneiro (2021)
The code of civil procedure of 2015 has as its great characteristic the search for procedural effectiveness with the satisfaction of the guardianship sought by the jurisdiction, efficiently and within a reasonable time. Despite other means for the realization of procedural effectiveness, this study will address only the typical coercive measures, since their application by the Courts has been suffering an effect different from that desired by the legislator. The objective is to outline the application of the periodic fine by the Courts, as well as the doctrinal position on the subject, even demonstrating that decisions against literal text of law have been prolatated to mitigate this coercive medium, given the majority jurisprudence that may reduce the value of the periodic fine won. This article will therefore give rise to a critical analysis of the legal interpretation of this coercive measure, demonstrating that, as applied, there is a clear reduction of its coertion to the debtor, directly influencing the fulfillment of the principle of effectiveness, so desired by the legislature of the Code of Civil Procedure of 2015. This study will therefore give rise to a critical analysis of the legal interpretation of this coercive measure, demonstrating that, as applied, there is a clear reduction of its coertion to the debtor, directly influencing the fulfillment of the principle of effectiveness, so desired by the legislator of the Code of Civil Procedure of 2015. As for the methodology, it is a descriptive-analytical study, with the development of bibliographic research. As for the type, books, articles and publications that deal with the theme addressed. The methodology is pure and qualitative and the objectives are descriptive, in order to clarify the problem, as well as exploratory, deepening the subjec